Selección de equipos y diseño del sistema para calentamiento de agua en un hotel cinco estrellas - Herrera Ordoñez., Manuel A. (2009)
The five stars hotels are companies dedicated to offer services, comfort and facilities to their customers while they are hosting in it. One of the services that hotels offer is hot water. This thesis has the aim to design the heat water system for a five stars hotel. This system works with steam. The design of this system includes thermal load calculation, boilers selection, water heaters selection, feed water system design, sizing of steam and condensates piping, fitting and steam traps selection, and sizing of the hot water storage tank. At this work, it is always considered that an efficient design results in a system with an economic and friendly operation with the environment and offer facilities when the maintenance is doing. Also, the implementation of this project would be in the most economic possible. At the end of this work, a cost analysis is shown which includes the value that it would be necessary to implement this project.